Investigation on a mini-CPC hybrid solar thermoelectric generator unit. (July 2016) - Dai, Y.J.; Hu, H.M.; Ge, T.S.; Wang, R.Z.; Kjellsen, Per
Abstract: A hybrid solar hot water and Bi2 Te3 -based thermoelectric generator (TEG) unit using a heat pipe evacuated tube collector with mini-compound parabolic concentrator (mini-CPC) is proposed. In this unit, the heat from the heat pipe evacuated tube solar collector is transferred to the hot side of TEG. Simultaneously, water cooling is used at the cold side to maintain the temperature difference. Electricity is generated by TEG and the remaining heat is transferred to water at the same time. This paper investigates how to convert excess solar heat into electricity more effectively. A mathematical model regarding this unit is developed and validated. It is found that the mini-CPC can significantly improve the electrical efficiency. The optimal thermal conductance of TEG is determined, which could make the best use of excess solar heat. The excess solar heat can be effectively converted into electricity when ZT of Bi2 Te3 can be improved from 100 °C to 200 °C. Using TEG with ZT = 1.0 and a geometrical concentrating ratio at 0.92, electrical and thermal efficiencies of this system are predicted to be 3.3% and 48.6% when solar radiation and water temperature are 800 Wm −2 and 20 °C, respectively. Highlights: A hybrid solar hot water and TEG unit is developed and modeled. A low cost mini-CPC is employed to significantly improve electrical efficiency. The optimal thermal conductance of TEG is determined. The unit can harvest the surplus heat for electricity. Experimental setup is built to validate the established mathematical model.